2000
DOI: 10.2134/agronj2000.921173x
|View full text |Cite
|
Sign up to set email alerts
|

Interference between Spring Cereals and Kochia scoparia Related to Environment and Photosynthetic Pathways

Abstract: Kochia [Kochia scoparia (L.) Schrad.; syn. Bassia scoparia (L.) A.J. Scott] is a weed that infests cereal crops in the Great Plains of the USA, often severely reducing yields. Herbicides have controlled kochia, but recently kochia has developed resistance to many herbicides. Nonherbicide alternatives are therefore needed for the integrated management of kochia. Greenhouse and growth chamber competition studies were conducted between kochia, a C4 weed, and barley (Hordeum vulgare L.) and wheat (Triticum aestivu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…They reported that weedy vegetation in Þelds that had been cultivated for Ͼ2 yr became dominated by nonnative weed species such as common lambsquarters, common chickweed, Stellaria media (L.) Cyrillo; quackgrass, Agropyron repens (L.) Beauv. ; and foxtail barley, Hordeum jubatum L. In addition, barley is known to be very competitive with weeds, requiring high densities of weeds to reduce yields (Conn and Thomas 1987, Lutman et al 1994, Christensen 1995, Fischer et al 2000, Walker et al 2001. In Alaska, Conn and Thomas (1987) reported a 36% reduction in barley yield in Alaska with 1,300 common lambsquarters seedlings per m 2 , much higher numbers than were encountered in the current study.…”
Section: Discussionmentioning
confidence: 41%
“…They reported that weedy vegetation in Þelds that had been cultivated for Ͼ2 yr became dominated by nonnative weed species such as common lambsquarters, common chickweed, Stellaria media (L.) Cyrillo; quackgrass, Agropyron repens (L.) Beauv. ; and foxtail barley, Hordeum jubatum L. In addition, barley is known to be very competitive with weeds, requiring high densities of weeds to reduce yields (Conn and Thomas 1987, Lutman et al 1994, Christensen 1995, Fischer et al 2000, Walker et al 2001. In Alaska, Conn and Thomas (1987) reported a 36% reduction in barley yield in Alaska with 1,300 common lambsquarters seedlings per m 2 , much higher numbers than were encountered in the current study.…”
Section: Discussionmentioning
confidence: 41%
“…As described previously, earlier spring emergence of the ALS inhibitor-HR cohorts may allow some selective control of HR vs. HS biotypes with spring seedbed preparation (tillage or herbicides) or by early spring frosts. In contrast to delayed seeding to reduce populations (Eberlein and Fore 1984), early seeding of spring crops is suggested to reduce the competitive ability of kochia (Fischer et al 2000). In a growth room study, shoot biomass of wheat was greater than kochia at 158C, but not at 23 or 308C, suggesting that early seeded spring wheat would have a competitive advantage over kochia (Nord et al 1999).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Some RYTs were relatively higher than 1.0. This response probably occurred primarily because of the reduced interference in mixtures in relation to the monocultures due to the differences in paths of resource acquisition (Fischer et al 2000) by C 3 rice plants and C 4 BYG plants, respectively.…”
Section: Shoot Dry Weightmentioning
confidence: 99%